2021
DOI: 10.1021/acsami.0c20509
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Improved Thermoelectric Energy Harvesting of Edge-Oxidized-Graphene-Bridged N-Type Bismuth Telluride Thick Films

Abstract: Power generation through the thermoelectric (TE) effect in small-sized devices requires a submillimeter-thick film that is beneficial to effectively maintain ΔT compared with a micron-scale thin film. However, most TE thick films, which are fabricated using printing technologies, suffer from low electrical conductivity due to the porous structures formed after sintering of the organic binder-mixed TE ink. In this study, we report an n-type TE thick film fabricated through bar-coating of the edge-oxidizedgraphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In ternary film, excepting the peaks of chalcopyrite, the characteristic D (∼1350 cm –1 ) and G bands (∼1585 cm –1 ) of graphene are observed, which are related to the vibrations of sp 3 -type disordered, activated carbon atoms and the sp 2 -like carbon atoms, respectively . A discernible decreased intensity of Raman peaks at 218.1 cm –1 , caused by the surface optical vibration, was observed in the ternary film, indicating the relaxation of the surface strain after the interaction between Cu 0.98 Zn 0.02 FeS 2 and graphene. ,, Figure c , d give the SEM-EDX analysis and the corresponding energy-dispersive X-ray spectroscopy of the ternary film. The mapping result confirmed that Cu, Zn, Fe, S, and C elements are uniformly distributed in the composite film.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In ternary film, excepting the peaks of chalcopyrite, the characteristic D (∼1350 cm –1 ) and G bands (∼1585 cm –1 ) of graphene are observed, which are related to the vibrations of sp 3 -type disordered, activated carbon atoms and the sp 2 -like carbon atoms, respectively . A discernible decreased intensity of Raman peaks at 218.1 cm –1 , caused by the surface optical vibration, was observed in the ternary film, indicating the relaxation of the surface strain after the interaction between Cu 0.98 Zn 0.02 FeS 2 and graphene. ,, Figure c , d give the SEM-EDX analysis and the corresponding energy-dispersive X-ray spectroscopy of the ternary film. The mapping result confirmed that Cu, Zn, Fe, S, and C elements are uniformly distributed in the composite film.…”
Section: Resultsmentioning
confidence: 91%
“…Taking into account that the electrical conductivity of inorganic materials will decrease when they are reduced in dimensionality and that the interfacial contact resistance is relatively high when incorporating them into the conductive polymer, many researchers have tried to address it by adding carbon allotropes. ,, The significant enhancement of the PF was observed because of the enhanced σ caused by the optimized carrier concentration and/or reduced void volume fraction between inorganic particles. Among these carbon allotropes, graphene, a one-atom-thick sp 2 -bonded planar carbon sheet, has frequently been considered as a promising filler to construct better conducting channels because of its higher theoretical surface area, high electrical conductivity, stable thermal properties, and excellent mechanical and chemical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of Bi 2 Te 3 -based TE materials needs a significant improvement and various strategies have been applied, like improving processing technique, [13,14] introducing defects, [15,16] nanoprecipitates, [17][18][19] structure texturing, [20,21] carrier energy filtering, [22,23] etc. [24][25][26][27] A strategy for dispersing GaAs nanoparticles into the Bi 2 Te 2.7 Se 0.3 have been proposed by Zhang et al, [28] which formed an appropriate interface barrier at phase boundaries in the GaAs/ Bi 2 Te 2.7 Se 0.3 (GaAs/BTS) composite system. Owing to the energydependent carrier scattering (EDCS) and enhanced phonon scattering, the interface barrier has increased Seebeck coefficient and an ultralow k L ~0.27 W m À 1 K À 1 (at 300 K) was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with well‐developed p‐type counterparts, the ZT ave and the corresponding conversion efficiency of the only room‐temperature commercial n‐type TE materials bismuth telluride (Bi 2 Te 3 )‐based TE alloys remain at a low level, which are the primary obstacles against energy harvesting and cooling applications. The performance of Bi 2 Te 3 ‐based TE materials needs a significant improvement and various strategies have been applied, like improving processing technique, [13,14] introducing defects, [15,16] nanoprecipitates, [17–19] structure texturing, [20,21] carrier energy filtering, [22,23] etc [24–27] . A strategy for dispersing GaAs nanoparticles into the Bi 2 Te 2.7 Se 0.3 have been proposed by Zhang et al, [28] which formed an appropriate interface barrier at phase boundaries in the GaAs/Bi 2 Te 2.7 Se 0.3 (GaAs/BTS) composite system.…”
Section: Introductionmentioning
confidence: 99%